2018
DOI: 10.4103/sajc.sajc_107_18
|View full text |Cite
|
Sign up to set email alerts
|

Practical consensus recommendatons for Paget’s disease in breast cancer

Abstract: Paget's disease of the breast is a rare type of cancer of the nipple–areola complex and that is often associated with an underlying in situ or invasive carcinoma. Diagnosis and treatment of Paget's disease is controversial. Expert oncologists discuss on the update on the approaches of Paget's disease diagnosis and its treatment options. This expert group used data from published literature, practical experience and opinion of a large group of academic oncologists to arrive at this practical consensus recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 35 publications
1
10
0
10
Order By: Relevance
“…MPD is a rare clinical entity, representing 1% to 3% of breast tumors [6]. MPD was first reported in 1856, by Velpau, when describing an eczematous lesion on the nipple's skin [7]. Later in 1874, Sir James Paget established an association between the presence of malignancy in the breast and dermatological changes in the nipple [3,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…MPD is a rare clinical entity, representing 1% to 3% of breast tumors [6]. MPD was first reported in 1856, by Velpau, when describing an eczematous lesion on the nipple's skin [7]. Later in 1874, Sir James Paget established an association between the presence of malignancy in the breast and dermatological changes in the nipple [3,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Pueden encontrarse micro calcificaciones "en perdigonada" de la región areolar. En diversos estudios, casi la mitad de los pacientes tienen mamografías normales [1][2][3][4][5][6][7].…”
Section: Discussionunclassified
“…Paget’s disease (PD) is an uncommon cutaneous intraepithelial malignancy characterized histopathologically by large epidermal adenocarcinoma cells (Paget’s cells) containing abundant mucin [ 1 ]. According to the affected anatomic locations, PD is classified as mammary Paget’s disease (MPD) and extramammary Paget’s disease (EMPD).…”
Section: Introductionmentioning
confidence: 99%
“…MPD is characterized by the eczematous eruption and ulceration of the nipple or areola [ 2 ]. The MPD incidence of all breast cancer (BC) is approximately 1%, and more than 90% of Paget’s disease of the nipple is associated with underlying intraductal carcinoma (DCIS) or infiltrating duct carcinoma (IDC) [ 1 , 3 ]. Recent studies have confirmed that MPD conjunction with invasive cancer had worse prognosis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%